2018
DOI: 10.2298/tsci171218162w
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on gas-liquid-coal fines three-phase flow in undulating pipeline

Abstract: Original scientific paper https://doi.org/10.2298/TSCI171218162WThe aggregation of coal fines particles at the bottom of the coal-bed methane well is a common occurrence during production, which could inhibit the flow in the bottom of wells and have adverse effect on the downhole equipment. In this work, gas-liquid-solid three-phase flow experiments were carried out to investigate the migration and discharge of coal fines particles in undulating pipeline. The experiments were conducted in downbent V-shaped pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is generally believed that the CPTF zone can be divided into three zones: crushed zone, crack zone, and vibration zone [17,19]. In order to further determine the range of the crack zone caused by phase transition fracturing, in this work, chromatographic analysis was performed on the gas extracted from the 14#, 26#, 31#, 3#, and 10# boreholes before and after fracturing, and the changes in CO 2 content from those boreholes before and after fracturing are observed and recorded.…”
Section: Radius Of Crack Zonementioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that the CPTF zone can be divided into three zones: crushed zone, crack zone, and vibration zone [17,19]. In order to further determine the range of the crack zone caused by phase transition fracturing, in this work, chromatographic analysis was performed on the gas extracted from the 14#, 26#, 31#, 3#, and 10# boreholes before and after fracturing, and the changes in CO 2 content from those boreholes before and after fracturing are observed and recorded.…”
Section: Radius Of Crack Zonementioning
confidence: 99%
“…Dong et al [16][17][18] studied the mechanism of CPTF, and calculated the equivalent weight of TNT. In addition, Wang et al [19,20] conducted the field tests and achieved an ideal penetration effect. Song et al [21] showed that the fractured radius of liquid CO 2 in coal seam is 12 m via field tests.…”
Section: Introductionmentioning
confidence: 99%